1956
DOI: 10.1121/1.1905138
|View full text |Cite
|
Sign up to set email alerts
|

Traffic Noise in West Germany, Evaluation of Noise Levels and Experience in Noise Control

Abstract: In 1932, Bakos and Kagan first attempted to measure traffic noise in Berlin. Later in 1938, Kösters and collaborators formed a “Map of Loudness” for Charlottenburg. At that early date they used a sound-level meter with weighting curves having frequency characteristics recommended by the German Acoustic Committee in 1937 and the logarithmic graphic level recorder of Braünmuhl. Many years later the PTB in Braunschweig and the Acoustics Laboratory in Düsseldorf began new traffic noise studies. In Düsseldorf we pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1968
1968
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It should then be possible to predict subjective response to road tra$c noise along motorways and in residential areas. Equivalent continuous sound level (¸C O ) and other indices have been used to describe the noise generated by road tra$c [1,2]. In his survey dealing with e!ects of road tra$c noise in Greater London under free-#ow conditions, Langdon [3] found that over the range of noise levels from 60 to 80 dB (A)¸ (the level exceeded or equalled for 10% of the measurement time), nuisance was found to be highly correlated with noise level measured as¸ over 24, 18 or 12 h and as¸C O over 24 h. Social surveys and "eld measurements [4] indicate a correlation between¸ , averaged over 18 h and human dissatisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…It should then be possible to predict subjective response to road tra$c noise along motorways and in residential areas. Equivalent continuous sound level (¸C O ) and other indices have been used to describe the noise generated by road tra$c [1,2]. In his survey dealing with e!ects of road tra$c noise in Greater London under free-#ow conditions, Langdon [3] found that over the range of noise levels from 60 to 80 dB (A)¸ (the level exceeded or equalled for 10% of the measurement time), nuisance was found to be highly correlated with noise level measured as¸ over 24, 18 or 12 h and as¸C O over 24 h. Social surveys and "eld measurements [4] indicate a correlation between¸ , averaged over 18 h and human dissatisfaction.…”
Section: Introductionmentioning
confidence: 99%